Evaluation of centers and improvement plans in the Autonomous Community of Aragon - Nieves Simón, Gema; Castán Esteban, José Luis; Mallada Bolea, Luis; Polo Martínez, Ignacio; Sánchez Estella, Óscar; Scott Taylor, Melanie (Avances en Supervisión Educativa, 2023)
The evaluation model of Aragon’s Education Inspection centers, which has been carried out since the 2014/2015 academic year, is presented. The application of the model is based on four basic principles: respect for autonomy, participation of the educational community, adaptation to the context, and pursuit of improvement. These principles are specified in several questionnaires that collect five areas of analysis of the reality of the centers (relational, resources, organizational-functional, teaching-learning planning, and teaching-learning development). Each of these areas integrates different dimensions that include specific aspects demanded by the different sectors of the educational community (teachers, inspectors, students, families). The conclusions are presented, and the difficulties of the model and the future that this action can have are indicated, aimed at generalizing the self-evaluation process by the centers through the model offered by this Educational Administration, improving the Inspection’s intervention in this process, and ensuring that any evaluation action that arises in an educational center is integrated into the same model and not as an isolated element without contextualization.